Interactive Theorem Proving 4th International Conference, ITP 2013, Rennes, France, July 22-26, 2013, Proceedings - Blazy, Sandrine; Paulin-Mohring, Christine; Pichardie, David (Theoretical Computer Science and General Issues, 2013)
This book constitutes the refereed proceedings of the 4th International Conference on Interactive Theorem Proving, ITP 2013, held in Rennes, France, in July 2013. The 26 regular full papers presented together with 7 rough diamond papers, 3 invited talks, and 2 invited tutorials were carefully reviewed and selected from 66 submissions. The papers are organized in topical sections such as program verfication, security, formalization of mathematics and theorem prover development.